Karakteristik Masyarakat Perkotaan di Komplek Depag Kota Serang Banten - Arini Teduh Alam Iskandar, Arini Teduh Alam Iskandar; khairunnisa tanjung, kharunnisa tanjung; Nyi Mas Melati Juniar, Nyi Mas Melati Juniar; Devia fitri Nurmahmudha, Devia fitri Nurmahmudha; Yogi Maulana Ardika, Yogi Maulana Ardika; Inarotul Wahdiyah, Inarotul Wahdiyah; Ino S Rawita, Ino S Rawita (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Society has a meaning, that is, a group of human beings interact with one another and need each other. This is because humans themselves are basically social beings. The aim is to identify the characteristics and habits of urban communities in the city of Serang. The author chooses to use qualitative methods in writing this article, which are supported by conducting interviews, observations and reinforced by literature studies. Urban communities themselves have various characteristics, this is due to cultural differences in in depth. The results in the field found differences in the characteristics of the people of Serang City in the Ministry of Religion complex with the characteristics of other urban communities with findings in the literature review which became the reference in writing this article.